A comparative study of Capacitor Placement Optimization (CAPO) and bus ranking method using PSS/Adept for IEEE 22 bus system network / Amirzaki Zahari - Zahari, Amirzaki (2009)
For the past few years a lot of methods have been searched to improve voltage regulation and reduce power losses in distribution system. This distribution system is the part which is connecting the distribution substation to the consumer service. This work research work focuses on comparison between Bus ranking method and Capacitor Placements Optimization (CAPO) applications to overcome these entire problems. The capacitor placement has been implemented in the network to minimize the total losses and improving the voltage stability. These two methods are to improve the voltage stability and reduction of power loss with additional capacitor at certain place in distribution system. Capacitor placement must determine the optimal location, type (fixed or switched), size and the control setting of capacitors to be installed on the distribution system. This method has been implemented using Power System Simulator/Advanced Distribution Engineering (PSS/Adept). PSS/Adept is used to model, simulate and analyse network in distribution system. Proposed method is implemented in the IEEE 33 Bus network. The effect of using Bus ranking method and CAPO application will show in this network within the result based on minimum voltage and total power losses. Based on the result obtained, it shows that by installing capacitor at suitable location with an appropriate sizing by using Bus ranking method there will be lower total power losses and higher voltage level in the distribution network. Bus ranking method gives better performances in order to improve objective of this research work.